Effects of Maneevej Exercise Technique on Exercise Behavior among Muslim Women in Narathiwat Province - ทองคุปต์, บุญยิ่ง; แวดือราแม, รังสฤษฎ์; กาเจ, ฟีเดีย; เจ๊ะเต๊ะ, มัสนีดา; อูมา, มารีนา; มามะ, มารีนา; ตันหยงขาเดร์, มัรยัม; ดีแม, มิสบ๊ะห์; หมันหลิน, มุสลีมะห์; เวาะสะ, มูนีเราะห์ (Princess of Naradhiwas University Journal, 2018)
This quasi-experimental research (one group pretest-posttest) aimed to compare exercise behavior before and after the use of Maneevej stretching exercise. Sample was 27 working-age women in Narathiwat Southern Muslim-majority Thai Province. Simple random sampling and purposive sampling were applied. The research tools used for data collection were a questionnaire divided into in three parts: knowledge, attitude, and practice about exercise, as well as a “stage of change” assessment form. Reliability of the questionnaire was analyzed using Kuder Richardson, and Cronbach’s alpha coefficients yielding values of 0.75, 0.76, and 0.78, respectively. The research tool used for the experiment was a VCD, and a training manual about the Maneevej stretching exercise. Its content validity was verified by 3 experts. The experiment was carried out for 1 month.The follow-up was conducted in the 2nd, the 3rd, and the 4th week of the experiment. Data were analyzed using descriptive statistics, and paired t-test. The results showed that, after the experiment, the mean scores of knowledge, attitude, and exercise behavior (M=11.8, S.D.=2.00, M=38.70, S.D.=3.57, and M=37.52, S.D.=3.09, respectively) were higher than before the experiment (M=7.11, S.D.=2.29, M=31.74, S.D.=3.58, and M=28.81, S.D.=3.49, respectively) with a statistical significance (t=15.83, 13.01, and 6.31, respectively, p < .001). Before the experiment, in terms of the stage of change, the majority of the sample (51.9%) was in the 2nd stage of change (contemplation about doing exercise), while after the experiment, a large majority of the sample (81.5%) was in the 3rd stage of change (preparation for doing exercise). The findings from this study suggest that the Maneevej stretching exercise should be promoted among Muslim women in order to increase their exercise behavior.